Thermal extremes in February and March 2024 in Poland and their synoptical background - Wrona, Katarzyna (Przegląd Geograficzny)
Extremes in air temperature are mostly studied with regards to summer period. However, the importance of above-average temperature in colder parts of the year should be highlighted too, as these extremes play an essential role for the phenological seasons and may also signalise the impacts of climate change. The aim of this work was to explore the uniqueness and synoptic background of abnormally warm February and March 2024 in Poland. The results show that during both months the inflow of rare tropical air masses determined the appearance of the highest temperature. However, the characteristics of the two months were different. During February, most days displayed the above-average daily mean temperature. In March, on the other hand, thermal situation was more complex. Both frost days and hot days were noted, with extreme minimum temperature often lower during March than in February. Under current state of knowledge, the results described in the paper represent very specific anomalies resulting from rare synoptic conditions, yet it is possible that due to climate change more events of this type will be noted in Poland and Central Europe.